Physical properties of rf magnetron sputter deposited NiO:WO3 thin films. (24th December 2014) - Usha, K S; Sivakumar, R; Sanjeeviraja, C; Ichimura, M
Abstract: The present study describes various physical properties of mixed nickel–tungsten oxide (NiO:WO3 ) (95:5) thin films prepared on glass substrate by rf magnetron sputtering due to the variation in rf power (100, 150, and 200 W). X-ray diffraction study shows that all the deposited films are amorphous in nature. The maximum transmittance of 97% in the infrared region was observed for the film deposited at 100 W rf power. A systematic reduction in the optical band gap is observed with increasing rf power, which is associated with the rf power induced effect leading to the production of localized states near the band edges of NiO:WO3 . The Urbach energy ( E U ) value was found to increase with rf power, which may be due to the increased defects in the NiO matrix. From the optical study, we have evaluated various parameters such as refractive index, packing density, lattice dielectric constant, ratio between free carrier density and free carrier effective mass, plasma frequency, and dispersion energy parameters, etc. These results are discussed and correlated well with the light of possible mechanisms underlying the phenomena. The compositional purity of the film was confirmed by energy dispersive x-ray analysis (EDAX) and Auger electron spectroscopic (AES) measurements. The Raman spectra of NiO:WO3 films show two peaks corresponding to one-phonon LO mode at 560 cm −1 and two-phonon LO mode at 1100 cm −1 due to the vibrations of Ni–O bonds and a strong peak at 860 cm −1 corresponds to the stretching vibration of W–O pair in the WO6 group. The band edge emission at 369 nm was observed in photoluminescence spectra.